2021
DOI: 10.1007/s00167-021-06701-w
|View full text |Cite
|
Sign up to set email alerts
|

Iliotibial band autograft is a suitable alternative graft for anterior cruciate ligament reconstruction: a systematic review and meta-analysis of outcomes

Abstract: Purpose Despite encouraging clinical, biomechanical and histological results, ACL reconstruction using the ITB was slowly abandoned. The hypothesis was that the current literature supports the use of ITB as the graft of choice for ACL reconstruction because of its good outcomes. Methods A systematic search of the literature was performed in the PubMed, MEDLINE, Cochrane, and Ovid databases to identify published clinical studies relevant to ACL reconstruction with ITB autograft and studies comparing ITB autogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Of the 2598 studies initially identified from the search strategy, a total of 50 systematic reviews (36 systematic reviews with meta‐analyses, 14 systematic reviews alone) were included in the final quality assessment (Figure 1) [1‐7, 10‐13, 16, 19, 21‐23, 25‐29, 31‐33, 35, 38‐42, 44, 46, 48, 52, 54, 58‐60, 65‐69, 71‐75, 77]. Cohen's κ Scores were 0.73, 0.75 and 0.74 at the title/abstract, full‐text screening and AMSTAR‐2 assessment stages, respectively, indicating substantial agreement at all phases of the review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 2598 studies initially identified from the search strategy, a total of 50 systematic reviews (36 systematic reviews with meta‐analyses, 14 systematic reviews alone) were included in the final quality assessment (Figure 1) [1‐7, 10‐13, 16, 19, 21‐23, 25‐29, 31‐33, 35, 38‐42, 44, 46, 48, 52, 54, 58‐60, 65‐69, 71‐75, 77]. Cohen's κ Scores were 0.73, 0.75 and 0.74 at the title/abstract, full‐text screening and AMSTAR‐2 assessment stages, respectively, indicating substantial agreement at all phases of the review.…”
Section: Resultsmentioning
confidence: 99%
“…The median number of studies included was 15 (IQR = 8.6-21.4) and the median number of total patients included was 1398 (IQR = 771.5-2024.5). Studies were published in 21 different journals, with the most common journals of publication being: The Journal of Arthroscopic and Related Surgery (nine studies; 18%) [4,5,10,11,13,25,32,54,60], The American Journal of Sports Medicine (seven studies; 14%) [6,16,22,23,48,67,69] and Knee Surgery, Sports Traumatology, Arthroscopy (six studies; 12%) [26,35,40,41,49,72]. The most commonly investigated comparison of autografts in included studies was HT versus BPTB (35/50, 70%), followed by QT versus HT versus BPTB (9/50, 18%), QT versus HT (3/ 50, 6%) and QT versus BPTB (1/50, 2%).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All ACLR techniques were analysed in association with LEAP. This decision was made because of the growing evidence supporting its use for reducing graft failure [13,14,16,18]. Additionally, ITBG, which inherently involves LEAPs, is commonly used in France and in our institution, and is recommended for cases requiring additional stabilisation for rotatory instability, such as athletes and individuals with high-risk knees [13,14,16,18].…”
Section: Discussionmentioning
confidence: 99%
“…This decision was made because of the growing evidence supporting its use for reducing graft failure [13,14,16,18]. Additionally, ITBG, which inherently involves LEAPs, is commonly used in France and in our institution, and is recommended for cases requiring additional stabilisation for rotatory instability, such as athletes and individuals with high-risk knees [13,14,16,18]. Although the choice of fixation for the same graft type varies, this study shows that the least amount of fixation clearly acts as the differentiating factor in terms of global impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation